จากทฤษฎีสู่การปฏิบัติ: โมเดลความเชื่อมโยงเชิงระบบของ 7 ปัจจัยหลักใน OBE และการประยุกต์ใช้ในวิทยาลัยศาสนศาสตร์ - โทอื้น, วรเชษฐ์; แสนภูมี, สมชัย (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 2 (2025): วารสาร มมร ยศสุนทรปริทรรศน์-ปีที่ 2 ฉบับที่ 2 (พฤษภาคม-สิงหาคม 2568), 2025)
This academic article is part of the research findings from the study entitled “The Development of Potential in Learning Skills and Outcome Based Education of Yasothon Buddhist college” Its purposes are to: (1) present the results of the study and analyze the systemic linkage of seven key factors in outcome-based education (OBE), namely educational philosophy, educational management, 21 st -century learning, OBE teaching, active learning, assessment and evaluation, and quality assurance; (2) identify the most influential factors contributing to the success of OBE implementation; and (3) develop an outcome-based learning manual tailored to the context of the theological college. The research employed a mixed-methods approach, collecting data from lecturers, students, and experts through questionnaires, in-depth interviews, and document analysis. The findings revealed that all seven factors are interconnected in a systemic manner, which supports the enhancement of teaching and learning quality in higher education. The three most influential factors were identified as OBE teaching, active learning, and competency assessment. These factors serve as critical drivers determining learner quality and competencies. Based on in-depth analysis, an evidence-based innovation—the outcome-based learning manual—was developed and proven to be effectively applicable to the context of Yasothon Buddhist college. This work holds both academic and practical value, particularly in curriculum development, instructional management, and quality assurance in 21 st -century education.